Ambipolar Organic Tri-Gate Transistor for Low-Power Complementary Electronics - Torricelli, Fabrizio (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.